Structures and Bonding Situation of Iron Complexes of Group‐13 Half‐Sandwich ECp* (E = B to Tl) Based on DFT Calculations. Issue 8 (28th April 2016) - Nguyen, Thi Ai Nhung; Huynh, Thi Phuong Loan; Tran, Thai Hoa; Pham, Van Tat; Duong, Tuan Quang; Dang, Tan Hiep
Abstract: Quantum chemical calculations at the BP86 level with various basis sets (SVP, TZVPP, and TZ2P+) were carried out for the Fe(CO)4 of group‐13 half‐sandwich E Cp* [Fe(CO)4 ‐ E Cp*] (Fe4‐ E ) ( E = B to Tl). The chemical bonding of the Fe(CO)4 ‐ E Cp* bond was analyzed with charge‐ and energy decomposition methods. The calculated equilibrium structures of complexesFe4‐ E show that the ligands E Cp* are bonded in an end‐on way to the fragment Fe(CO)4 inFe4‐ E with E = B to Ga. The compoundFe4‐In has a distorted end‐on ligand InCp*. In contrast, Fe4‐Tl has a side‐on bonded ligand TlCp*. The calculated bond dissociation energies (BDEs) suggest that the bond in the iron group‐13 half‐sandwich complexesFe4‐ E decreases fromFe4‐B toFe4‐Tl . Natural bond orbital (NBO) analysis of the bonding situation reveals that the Fe(CO)4 ← E Cp* donation inFe4‐ E comes from the σ lone‐pair orbital of E Cp*. Bonding analysis indicates that the ligand E Cp* in complexes are strong σ donors and the NOCV pairs of the bonding show small π‐back donation from the Fe(CO)4 to the E Cp* ligands. Abstract :